Cloning, expression, purification, crystallization and preliminary X-ray studies of the C-terminal domain of Rv3262 (FbiB) from Mycobacterium tuberculosis - Mohamed Rehan, Aisyah; Paterson, Neil G.; Baker, Edward N.; Squire, Christopher J. (Wiley-Blackwell Publishing, Inc., 2011)
During cofactor F420 biosynthesis, the enzyme F420-[gamma]-glutamyl ligase (FbiB) catalyzes the addition of [gamma]-linked L-glutamate residues to form polyglutamylated F420 derivatives. In Mycobacterium tuberculosis, Rv3262 (FbiB) consists of two domains: an N-terminal domain from the F420 ligase superfamily and a C-terminal domain with sequence similarity to nitro-FMN reductase superfamily proteins. To characterize the role of the C-terminal domain of FbiB in polyglutamyl ligation, it has been purified and crystallized in an apo form. The crystals diffracted to 2.0 Å resolution using a synchrotron source and belonged to the tetragonal space group P41212 (or P43212), with unit-cell parameters a = b = 136.6, c = 101.7 Å, [alpha] = [beta] = [gamma] = 90°.